The Sociological Structures in the Two Collections Blood and Mud by Yahya Haqqi and Isn’t It? By Youssef Idris - Al-Jalimi, Hamad (Journal of Umm Al-Qura University for Language Sciences and Literature, 2024)
This research monitors the sociological structures in my collection: “Blood and Mud” by Yahya Haqqi, and “Isn’t It?” By Youssef Idris, it examines the social, ideological and cultural transformations that their era witnessed, and discusses the structures that are the focus of their topics, such as the conflict between women and men, acceptance and rejection, dream and reality, and shows the aspects of alliance and difference between them. It also deals with the visions that emerged from the environment, and depicts their transformation into external visions. External or internal visions; In line with the internal conflicts in the text, the research did not ignore the study of the multiplicity of voices, the role of the narrator or the characters in presenting their ideas about society and its problems, the use of temporal and spatial space, and the use of two languages: standard and dialect in narrative construction.